EGFR is a pivotal regulator of thrombin-mediated inflammation in primary human nucleus pulposus culture - Bor-Ren Huang (Nature Portfolio, 2017)
Abstract We found that the coagulation and cytokine pathways were important mechanisms involve in the degeneration of intervertebral discs (IVD) using a microarray approach to analyze gene expression in different grades of specimens. Furthermore, using a cytokine/chemokine array, a significant increase in CXCL8 expression was observed in human nucleus pulposus (NP) cells after thrombin treatment. The enhancement of CXCL8 expression by thrombin was activated by the PAR1 receptor. Importantly, analysis of degenerated human NP tissue samples showed that EGFR expression positively correlated with the grade of tissue degeneration. In NP cells, thrombin caused an increase in phosphorylation of the EGFR at the Tyr1068, and treatment with the pharmacological EGFR inhibitor, AG1473 effectively blocked thrombin-enhanced CXCL8 production. Surprisingly, inhibition of STAT3 for 24 h decreased expression of EGFR. Treatment with thrombin also increased Akt and GSK3α/β activation; this activation was also blocked by EGFR inhibitor. Although c-Src, ERK, and FAK were activated by thrombin, only c-Src and ERK were involved in the STAT3/CXCL8 induction. Our findings indicate that stimulation of an inflammatory response in NP cells by thrombin is part of a specific pathophysiology that modulates the EGFR activation through activation of Src/ERK/STAT3 signaling.